Exploring views of members of the public and policymakers on the acceptability of population level dietary and active-travel policies: a qualitative study - Toumpakari, Zoi; Valerino-Perea, S.; Willis, K.; Adams, J.; White, M.; Vasiljevic, M.; Ternent, L.; Brown, J.; Kelly, M. P.; Bonell, C.; Cummins, S.; Majeed, A.; et al. (International journal of behavioral nutrition and physical activity, 2023)
Background: There is limited evidence on what shapes the acceptability of population level dietary and active-travel policies in England. This information would be useful in the decision-making process about which policies should be implemented and how to increase their effectiveness and sustainability. To fill this gap, we explored public and policymakers’ views about factors that influence public acceptability of dietary and active-travel policies and how to increase public acceptability for these policies. Methods: We conducted online, semi-structured interviews with 20 members of the public and 20 policymakers in England. A purposive sampling frame was used to recruit members of the public via a recruitment agency, based on age, sex, socioeconomic status and ethnicity. Policymakers were recruited from existing contacts within our research collaborations and via snowball sampling. We explored different dietary and active-travel policies that varied in their scope and focus. Interviews were transcribed verbatim and analysed using thematic reflexive analysis with both inductive and deductive coding. Results: We identified four themes that informed public acceptability of dietary and active-travel policies: (1) perceived policy effectiveness, i.e., policies that included believable mechanisms of action, addressed valued co-benefits and barriers to engage in the behaviour; (2) perceived policy fairness, i.e., policies that provided everyone with an opportunity to benefit (mentioned only by the public), equally considered the needs of various population subgroups and rewarded ‘healthy’ behaviours rather than only penalising ‘unhealthy’ behaviours; (3) communication of policies, i.e., policies that were visible and had consistent and positive messages from the media (mentioned only by policymakers) and (4) how to improve policy support, with the main suggestion being an integrated strategy addressing multiple aspects of these behaviours, inclusive policies that consider everyone’s needs and use of appropriate channels and messages in policy communication. Conclusions: Our findings highlight that members’ of the public and policymakers’ support for dietary and active-travel policies can be shaped by the perceived effectiveness, fairness and communication of policies and provide suggestions on how to improve policy support. This information can inform the design of acceptable policies but can also be used to help communicate existing and future policies to maximise their adoption and sustainability.
Gesehen am 06.07.2023